2009
DOI: 10.1073/pnas.0809997106
|View full text |Cite
|
Sign up to set email alerts
|

NAADP-mediated Ca 2+ signaling via type 1 ryanodine receptor in T cells revealed by a synthetic NAADP antagonist

Abstract: The nucleotide NAADP was recently discovered as a second messenger involved in the initiation and propagation of Ca 2؉ signaling in lymphoma T cells, but its impact on primary T cell function is still unknown. An optimized, synthetic, small molecule inhibitor of NAADP action, termed BZ194, was designed and synthesized. antagonism ͉ nucleotide ͉ second messenger ͉ synthesis

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
161
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 106 publications
(171 citation statements)
references
References 46 publications
9
161
0
1
Order By: Relevance
“…Thus, the reprogramming of freshly activated T cells to a "migratory" phenotype could be one target along these lines. Indeed, the NAADP antagonist, BZ194, which efficiently blocks intracellular calcium signaling (38), ameliorates clinical EAE both by prophylactic and therapeutic application (18). In this study intravital imaging revealed that BZ194 reduced the frequency of long-lasting calcium signaling in the T cells at the spinal cord leptomeninges (Fig.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Thus, the reprogramming of freshly activated T cells to a "migratory" phenotype could be one target along these lines. Indeed, the NAADP antagonist, BZ194, which efficiently blocks intracellular calcium signaling (38), ameliorates clinical EAE both by prophylactic and therapeutic application (18). In this study intravital imaging revealed that BZ194 reduced the frequency of long-lasting calcium signaling in the T cells at the spinal cord leptomeninges (Fig.…”
Section: Discussionmentioning
confidence: 86%
“…BZ194 Treatment. BZ194 was synthesized and purified as previously described (38) and checked for homogeneity by HPLC, NMR, and high-resolution mass spectrometry. BZ194 (180 mg/kg in DMSO) was injected intraperitoneally daily starting from day 0 after EAE induction.…”
Section: Methodsmentioning
confidence: 99%
“…InsP 3 and cADPR act at the endoplasmic and sarcoplasmic reticulum via InsP 3 and ryanodine receptors (RyRs), respectively. In contrast, the NAADP signaling cascade is more controversial, with action reported at both RyRs on the endo-or sarcoplasmic reticulum (5)(6)(7)(8), and two-pore channels (TPCs) on acidic stores having been described (9)(10)(11).…”
mentioning
confidence: 99%
“…Controversy surrounds both the identity of the NAADP-activated channel and its organellar location. There is evidence for the NAADP receptor being the transient receptor potential mucolipin 1 channel (10), the ryanodine receptor (11,12), or the two-pore channel (Refs. [13][14][15]; for review, see Ref.…”
Section: Camentioning
confidence: 99%